Hydrothermal Synthesis and Characterization of Flower-like SnO2-Zn2SnO4 Nanocomposites - Li, Zi-Rong; Cheng, Guo-Jun (Asian Journal of Chemistry, 2013)
Flower-like SnO2-Zn2SnO4 nanocomposites were prepared via a simple hydrothermal process. X-ray diffraction patterns show that as-prepared sample is the composite of SnO2 and Zn2SnO4. Transmission electronmicroscopy characterizations confirm that the morphologies of SnO2 and Zn2SnO4 nanocomposites are "flower". Photoluminescence measurement of the SnO2-Zn2SnO4 nanocomposites reveals a stable purple emission band centered at ca. 440 nm. The influences of the hydrothermal temperature and time, the molar ratio of Zn2+ and Sn4+ and the concentrations of NaOH have been studied. The possible growth mechanisms of flower-like nanocomposites and the possible reaction process were discussed.